ChemInform Abstract: Highly Modular C1‐Symmetric Chiral (P, N) Ligands with a Stereolabile P Center: Experimental and Theoretical Studies. Issue 26 (1st July 2014) - Humbert, Nicolas; Larionov, Evgeny; Mantilli, Luca; Nareddy, Pradeep; Besnard, Celine; Guenee, Laure; Mazet, Clement
Abstract Several chiral P, N‐ligands are synthesized and tested in two model reactions.